The plate test carried out on fresh cement-based materials:How and why?. (March 2017) - Amziane, S.; Perrot, A.
Abstract: The plate test consists in measuring the mass variation of a rough tool (plate or cylinder) immersed in a fresh cement-based material with time. It has been used to study the evolution of the rheological behavior of cement-based materials with time. This device was initially developed to enable a simple measurement of the increase of the yield stress. Therefore, it can provide an accurate value of the structuration rate during the so-called dormant period and also provide an evaluation of the initial setting time. However, as the immersed tool remains static, the success of the test depends on the movement of the cement-based material at the interface. The relative translation between the freshly made cement-based material and the tool must be sufficient to overcome the critical shear strain of the sample. During the very early age of the cement-based material many phenomena occur (consolidation, shrinkage, thermal expansion, bleeding…) and lead to volume variation of the material. Those volume variations need to be controlled in order to ensure a correct measurement of the yield stress. After providing and explaining the test physical background and procedure, we first aim to warn researchers about possible measuring artefacts that lead to a too low strain at the tool interface. Then, this paper shows all the possibilities and information provided by during the dormant period and setting. In this paper, an attempt to extend the test duration and to get also information on the thermal expansion is presented. This paper shows how to perform a successful and highlights the versatility of the plate tests that is able to provide interesting information about structural build-up, setting and thermal expansion.